Effect of Intravitreal Ranibizumab on Intraretinal Hard Exudates in Eyes with Diabetic Macular Edema - Srinivas, Sowmya; Verma, Aditya; Nittala, Muneeswar G.; Alagorie, Ahmed Roshdy; Nassisi, Marco; Gasperini, Julie; Sadda, SriniVas R. (American journal of ophthalmology, 2020)
To study the effect of monthly 0.3-mg intravitreal ranibizumab injections on intraretinal hard exudates (HEs) and correlate the effect with macular thickness in eyes with diabetic macular edema (DME). Randomized, controlled trial. Twenty-four eyes of 24 subjects with DME were included in this institutional review board–approved, prospective longitudinal study. Subjects were randomly assigned to receive monthly intravitreal ranibizumab injections either until macular edema resolved or until both macular edema and HEs resolved. All subjects underwent spectral-domain optical coherence tomography imaging (Cirrus OCT), at baseline and monthly for 12 months. Mean HE area and mean macular thickness at baseline and month 12 were compared using a paired t test and correlated with Pearson analysis. The average age of the 24 subjects was 65 (±8.55) years. There was a significant decrease (P = .001) in mean HE area from baseline (0.48 ± 0.43 mm2) to month 12 (0.17 ± 0.19 mm2). There was a significant increase (P < .001) in best-corrected visual acuity from a letter score of 63.38 (±7.92) at baseline to 76.38 (±8.93) at month 12. There was no additional vision benefit for continuing to treat with monthly injections for persistent HE in the absence of macular thickening. In eyes with DME, monthly intravitreal ranibizumab injections resulted in significant reduction in intraretinal HEs that paralleled reductions in macular thickness and volume. Baseline foveal HEs were associated with worse vision outcomes, and continued treatment for persistent HEs in the absence of edema did not result in better vision.